THE EFFECT OF SERVICE QUALITY ON RE-BUYING IN LAZADA'S ONLINE SHOPPING WITH CUSTOMER SATISFACTION AS A MEDIATION VARIABLES SERVICE QUALITY, CUSTOMER SATISFACTION, AND REPURCHASE INTEREST. - Rosita Wahyuni (Faculty of Islamic Economics and Business, 2021)
This study aims to test: 1). The Effect of Service Quality on Repurchase Intention. 2). Effect of Service Quality on Customer Satisfaction. 3). The Effect of Consumer Satisfaction on Repurchase Interest. 4). The Effect of Service Quality on Repurchase Interest is mediated by Customer Satisfaction. The sampling technique used non-probability sampling method, namely accidental sampling, with a sample of 150 respondents. The analysis method used is simple linear regression and multiple linear regression. The data used are primary data using a questionnaire for data collection. Based on the results of data analysis, it shows that Service Quality (X) has a positive effect on Repurchase Interest (Y). Service Quality (X) has a positive effect on Customer Satisfaction (Z). Consumer Satisfaction (Z) has a positive effect on Repurchase Interest (Y). Customer Satisfaction (Z) fully mediates between Service Quality (X) and Repurchase Interest (Y). This is because when a comparison is made between the direct effect and the indirect effect, the coefficient value of Service Quality (X) has decreased and the significance value, which was initially significant, becomes insignificant.